PERAN INKUBATOR BISNIS DALAM PENGEMBANGKAN STARTUP PADA PERGURUAN TINGGI - Mohammad Habibi (ICO EDUSHA, 2022)
Startups are sufficiently growth in Indonesia to become a trend in business incubators that include college or university students. This is due to the incubationconcept and program offered to prospective entrepreneurs who have potential ideas inbusiness. Thus, research was conducted to determine the role of business incubators indeveloping startups in universities. But there are obstacles in developing startups,limited technology, leadership and management. The study was conducted at thePPKIB Incubator of STAINIM with a qualitative approach. The research method usedis the method of observation and literature review by collecting data that aims tosimplify the process. It can be seen how the government encourages businessincubators in developing startups and introducing business through technology. Theresearch objective is to increase innovation or creativity in developing successful newstartups in higher education. Seen from students utilizing the facilities at the AlphabetIncubator to develop small businesses in the digital industry to increase the workforce. Keywords: Business Incubator; Startup; Innovation or Creativity References Alimudin, Arasy. “Strategi Pengembangan Minat Wirausaha Melalui Proses Pembelajaran.” E-Jurnal Manajemen Kinerja 1, no. 1 (2015): 1–13. Baskoro, M Lahandi, and Maulidian Maulidian. “Pelatihan Instagram Marketing Untuk Tenant Inkubator Bisnis Trilogi.” Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal 2, no. 1 (2019): 19–26. Bismala, L, and S Handayani. “Core Competency Factors and Sme’s Competitive Strategy.” International Journal of Recent Scientific Research 8, no. 9 (2017): 20257–20261. Budiyanto, Hery, Agus Suprapto, and Dina Poerwoningsih. “Program Pengembangan Kewirausahaan Dalam Bentuk Inkubator Bisnis Di Perguruan Tinggi Bagi Mahasiswa Pemilik Usaha Pemula.” In Seminar Nasional Sistem Informasi (Senasif), 1:385–394, 2017. Elmansori, E, and Leslie Arthur. “Entrepreneurship and SMEs through Business Incubators in the Arab World: Case Study of Jordan.” Journal of Business and Economics 6, no. 10 (2015): 1791–1800. Hamdan, Hamdan. “Model Inkubator Bisnis Untuk Menumbuhkan Kompetensi Kewirausahaan.” Jurnal Penelitian Pendidikan 13, no. 1 (2013). Jaya, Mardi Arya, Ridi Ferdiana, and Silmi Fauziati. “Analisis Faktor Keberhasilan Startup Digital Di Yogyakarta.” Prosiding Snatif (2017): 167–173. KUKM, Kementerian. “Kementerian Koperasi Dan Usaha Kecil Dan Menengah” (2012). Kurniasari, Fita, and Eka Wira Putra. “Model Pembelajaran Industrial Incubator Based Learning (IIBL) Untuk Mengembangkan Jiwa Kewirausahaan Mahasiswa Universitas Muhammadiyah Pontianak.” Pena Kreatif: Jurnal Pendidikan 7, no. 2 (2018): 53–59. Mahani, Septiana Ayu Estri. “Tinjauan Model Inkubator Bisnis Rintisan (Bisnis Start up) Di Indonesia.” Jurnal Manajemen dan Bisnis (Performa) 12, no. 1 (2015): 76–95. Nurdianto, Alifian Bayu. “Optimalisasi Wakaf Untuk Inkubator Bisnis Dan Teknologi Usaha Mikro Kecil Menengah (UMKM) Di Sidoarjo.” ISTISMAR 1 (2018): 43–49. Putra, Ryan Aditya, and Herminanto Sofyan. “Partisipasi Industri Otomotif Dalam Implementasi Work Based Learning Di SMK Daerah Istimewa Yogyakarta.” E-Jurnal Pendidikan Teknik Otomotif-S1 19, no. 1 (2017). Rofieq, Mochammad, Ditya Permatasari, and Lailatul Farida. “Model Pendampingan Umkm Bidang Kerajinan Menjadi Start-Up Sukses Di Kota Malang.” Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang 3, no. 2 (2018): 1–8. Saleh, Amiruddin, and Ujang Sehabudin. “Pengembangan Program Inkubator Wirausaha Sosial Di Kecamatan Cibungbulang, Kabupaten Bogor.” Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat 1, no. 2 (2015): 88–95. Siregar, Gustina, Dewi Andriany, and Lila Bismala. “Program Inkubasi Bagi Tenant Inwall Di Pusat Kewirausahaan, Inovasi Dan Inkubator Bisnis Universitas Muhammadiyah Sumatera Utara.” In Prosiding Seminar Nasional Kewirausahaan, 1:45–51, 2019.